Obesity Alters the Vascular Morphology and VEGF‐A Signaling in Adipose Tissue - Yunjeong Lee; Keith Lionel Tukei; Yingye Fang; Shobhan Kuila; Xinming Liu; Princess I. Imoukhuede (FASEB BioAdvances)
ABSTRACT Obesity is a global health crisis, with its prevalence particularly severe in the United States, where over 42% of adults live with obesity. Obesity is driven by complex molecular and tissue‐level mechanisms that remain poorly understood. Among these, angiogenesis—primarily mediated by vascular endothelial growth factor‐A (VEGF‐A)—is critical for adipose tissue expansion but presents unique challenges for therapeutic targeting due to its intricate regulation. Systems biology approaches have advanced our understanding of VEGF‐A signaling in vascular diseases, but their application to obesity is limited by scattered and sometimes contradictory data. To address this gap, we performed a comprehensive analysis of the existing literature to synthesize key findings, standardize data, and provide a holistic perspective on the adipose vascular microenvironment. The data mining revealed five key findings: (1) obesity increases adipocyte size by 78%; (2) vessel density in adipose tissue decreases by 51% in mice with obesity, with vessels being 47%–58% smaller and four to nine times denser in comparison with tumor vessels; (3) capillary basement membrane thickness remains similar regardless of obesity; (4) VEGF‐A shows the strongest binding affinity for VEGFR1, with four times stronger affinity for VEGFR2 than for NRP1; and (5) binding affinities measured by radioligand binding assay and surface plasmon resonance are significantly different. These consolidated findings provide essential parameters for systems biology modeling, new insights into obesity‐induced changes in adipose tissue, and a foundation for developing angiogenesis‐targeting therapies for obesity.